Shell Script to Clone AODV Routing Protocol in Network Simulator-2 - Ulla Khan, Roshan; A. PhD, Vijayalakshmi (International Journal of Engineering and Technology, 2018)
Background and Objective: Most of the research that are carried in ad hoc routing protocol is through simulation. While working with a simulator, the codes are enclosed in a component that is accessible to all the developers. The difficulty arises as there is no enough documentation and users find it difficult to modify different C++ and TCL files. Even if one component is modified then the entire Network Simulator-2 (NS-2) suite must be reconfigured. Cloning the protocol manually takes a lot of time and prone to error. Our objective is to ease the work of developers and researchers by showing the procedure to clone the AODV protocol automatically using a script. Methodology: In this study, a shell script is developed that will clone the AODV protocol by modifying 18 C++ and TCL files of the protocol and NS-2 suite by automatically inserting the code in exact files at exact position. It also configures the NS-2 and installs the entire NS-2 suite along with setting the path in .bash files. Results: In this research work, a comparison of cloned protocol with AODV protocol is done based on throughput time and packet loss metrics and the results generated are exactly same for both the protocols. The results of the study reveal that the proposed script clones the AODV protocol successfully. Conclusion: This work proves that the proposed script can clone the AODV protocol faster with just one execution of shell script. This methodology will save the time and help the developers or research to focus more on their study on the protocol.Â